Redaksi & Pedoman Penulisan Jurnal Media Teknik Sipil Vol12, No.2, Agustus 2015 - Redaksi & Pedoman Penulisan Jurnal (Media Teknik Sipil, 2014)
Redaksi & Pedoman Penulisan Jurnal Media Teknik Sipil Vol12, No.2, Agustus 2015jurnal.mediatekniksipil.umm@gmail.com